2012
DOI: 10.1155/2012/193496
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobiology and Ethnopharmacology ofLepidium meyenii(Maca), a Plant from the Peruvian Highlands

Abstract: Lepidium meyenii (maca) is a Peruvian plant of the Brassicaceae family cultivated for more than 2000 years, which grows exclusively in the central Andes between 4000 and 4500 m altitude. Maca is used as a food supplement and also for its medicinal properties described traditionally. Since the 90s of the XX century, an increasing interest in products from maca has been observed in many parts of the world. In the last decade, exportation of maca from Peru has increased from 1,415,000 USD in 2001 to USD 6,170,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 63 publications
0
96
1
9
Order By: Relevance
“…Their pharmaceutical form was powder (4), capsule (6), tablet (2), ampoule (1), and spray (1). In case of monocomponent preparations (1-5 products) the recommended daily posologies (1500-5000 mg dry hypocotyl powder) overlap with the effective dosages used in human studies (QUIRÓS & ALIAGA, 1997;WANG et al, 2007;GONZALES, 2012), but for multicomponent products (6-14.) are much lower, between 80-125 mg for 4 products, 500 and 750 mg in two cases, and not declared in one case.…”
Section: Product Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Their pharmaceutical form was powder (4), capsule (6), tablet (2), ampoule (1), and spray (1). In case of monocomponent preparations (1-5 products) the recommended daily posologies (1500-5000 mg dry hypocotyl powder) overlap with the effective dosages used in human studies (QUIRÓS & ALIAGA, 1997;WANG et al, 2007;GONZALES, 2012), but for multicomponent products (6-14.) are much lower, between 80-125 mg for 4 products, 500 and 750 mg in two cases, and not declared in one case.…”
Section: Product Analysismentioning
confidence: 99%
“…In a similar experiment maca was inactive, but the cause of this could be the much lower dosage (LENTZ et al, 2007). Some clinical trials have been shown that long-term (4-6 weeks) consumption of dry maca hypocotyl with a 1.5-3 g daily dosage leads to the enhancement of sexual activity and fertility of men and women, too (BROOKS et al, 2008;SHIN et al, 2010;GONZALES, 2012). However, these studies were too heterogeneous and the number of the participants too low to make a fi rm conclusion.…”
mentioning
confidence: 98%
“…Cannabinoid and cholinergic systems [20,21], as well as redox unbalance [22][23][24][25], play a relevant role in persistent pain processes. Maca consumption has been associated with lower serum levels of the proinflammatory and proalgic cytokine IL-6 in populations living in the Peruvian Central Andes [8]. Starting from the theoretical approach that maca is able to modulate endogenous systems normally involved in pain control, the aim of this study was to evaluate the efficacy, after acute intake (oral administration), of a commercial water extract of L. meyenii, controlled in its composition by high performance liquid chromatography with diode array detector (HPLC-DAD) and high performance liquid chromatography-mass spectrometry (HPLC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The tubers of L. meyenii have been widely investigated during these last years, pointing out the copresence of two main groups of phytochemicals, the glucosinolates and the macamides and macaenes. The first group is typical of Brassicaceae; in maca, the main forms are aromatic glucosinolates [7], suggested by some authors as chemical markers to explain some biological effects of this plant [8] and denied by others. Over the last few years, different studies that have focused on the analysis and purification of macamides from this plant have been available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Currently, herbal therapies and medical foods provide prospective alternative/complementary strategies for the treatment of depression. Maca (Lepidium meyenii), a plant that grows indigenously at an altitude of more than 4000 m in the central Peruvian Andes, 15 is believed to have great benefits for the treatment of depression. It has been used by indigenous Andeans for thousands of years as a foodstuff, and is now used worldwide as a food supplement and medicine.…”
Section: Introduction Dmentioning
confidence: 99%